Implementation of Project Based Learning in Mechatronic Lab Course at Bandung State Polytechnic - Noor Cholis Basjaruddin; Edi Rakhman (International Journal of Evaluation and Research in Education (IJERE), 2016)
Mechatronics is a multidisciplinary that includes a combination of mechanics, electronics, control systems, and computer science. The main objective of mechatronics learning is to establish a comprehensive mindset in the development of mechatronic systems. Project Based Learning (PBL) is an appropriate method for use in the learning process of mechatronic. The use of PBL by following the V model in  system development process is expected to encourage the achievement of the main goal of learning in mechatronics lab. Demonstration of knowledge during the practical work done by drafting product development procedures documents, presentations, and project demo. The test result of mechatronics lab course based on PBL in Electronics Engineering Bandung State Polytechnic led to the conclusion that the model is acceptable and desirable to be passed with a few improvements. In addition, learners also feel there is a new challenge in following the PBL-based practicum.